Stabilisasi Tanah Lempung Kerobokan Dengan California Bearing Ratio (CBR) Untuk Perkerasan Jalan Raya - Ni Ketut Sri Astati Sukawati; I Made Juniastra; I Made Sastra Wibawa; I Gede Ngurah Sunatha; I Made Nada (Postgraduate, University of Mataram, 2024)
In this research, clay soil will be stabilized in the Kerobokan Badung area by mixing the soil with various levels of lime. The problem to be solved is how much the CBR value of soil mixed with lime will increase and what is the most economical lime content associated with the minimum CBR requirements for the base soil layer. The aim is to determine the increase in CBR value from a mixture of clay with lime and to determine the most economical lime content associated with the minimum CBR requirements for the base layer of highway pavement structures. The research results show that adding lime to clay soil can increase its bearing capacity. For the standard compaction method, the CBR of the base soil which was initially 3.32% increased to 12.14, 21.86, and 26.24% for lime addition of 2.50, 5.00, and 10.00% respectively. For the modified compaction method, the CBR of the base soil which was initially 5.74% increased to 13.42, 25.69, and 38.15% for lime addition of 2.50, 5.00, and 10.00% respectively. To produce a base soil CBR of 6%, the modified compaction method requires less lime content than the standard method. The lime content required is 0.22% for modified compaction and 0.79% for standard compaction.